A large-sized, high-purity α″-Fe 16 Preparation method of N2 iron nitride magnetic powder

Iron concentrate activated by high-pressure roll milling and nano-sand milling, combined with low-temperature hydrogen reduction and nitriding technology, high-purity, large-size α″-Fe16N2 ferromagnetic nitride powder was prepared, solving the difficulty in preparing high-purity in the prior art. The problem of micron-scale particle size α″-Fe16N2 realizes the preparation of materials suitable for high-performance magnets.

CN118954444BActive Publication Date: 2024-12-27CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411452888.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-27
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

It is difficult to prepare high-purity, micron-scale large-size α″-Fe16N2 ferromagnetic nitride powder, and its stability is poor at high temperatures, making it difficult to meet the needs of high-performance magnets.

Method used

Iron concentrate is synergistically activated by high-pressure roll mill and nanosand mill to prepare porous active micron-scale iron particles, and the reaction conditions are controlled during low-temperature hydrogen reduction and nitriding to obtain high-purity large-size α″-Fe16N2 ferromagnetic nitride with high purity powder.

Benefits of technology

Achieve the preparation of α″-Fe16N2 ferromagnetic powder with high purity (over 97%) and large size (micron scale), with excellent magnetic properties, suitable for replacement of rare earth permanent magnets, suitable for electric vehicles and wind power generation High-performance magnet applications such as facilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118954444B_ABST
    Figure CN118954444B_ABST
Patent Text Reader

Abstract

The invention discloses a large-size high-purity α"-Fe 16 The method for preparing N2 nitrided iron magnetic powder comprises the following steps: 1) subjecting iron concentrate to high pressure roller milling, nano sand milling and drying treatment in sequence to obtain micron-sized fine particle iron oxide powder; 2) subjecting the micron-sized fine particle iron oxide powder to hydrogen reduction to obtain porous active reduced iron powder; the temperature of the hydrogen reduction is controlled to be within the range of 50°C below the critical temperature of the reduction conversion path; 3) subjecting the porous active reduced iron powder to nitridation in an ammonia atmosphere to obtain α″-Fe 16 N2 iron nitride, this method uses cheap iron concentrate as raw material, has low cost, simple process, can be mass-produced, and can obtain micron-level high-purity α″-Fe 16 N2 iron nitride powder can then be formed using conventional additive manufacturing methods to produce high-performance magnets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an α″-Fe 16 Preparation method of N2 iron nitride magnetic powder, particularly a method for preparing large-sized α"-Fe by synergistic activation of high-pressure roller mill and nano sand mill 16 The invention relates to a method for nitriding iron powder with N2, and belongs to the technical field of preparing magnetic powder materials. Background Art

[0002] Permanent magnetic materials are widely used. The current high-quality permanent magnetic materials are made of rare earth permanent magnets represented by Nd-Fe-B, which have high coercive force. However, the maximum magnetic energy product (BH)max is limited by the low Ms value of the rare earth compound itself, and cannot achieve a greater breakthrough, especially limiting its application in high-tech industries such as electric vehicles and wind power generation facilities. In addition, the rare earth metal elements required for rare earth permanent magnets are expensive and face the risk of resource depletion, and their mining volume is difficult to meet the needs of the rapidly developing new energy field. Therefore, the development of new zero-rare earth high-performance permanent magnetic materials is undoubtedly an important guarantee for solving future energy problems. At present, iron nitride is the most likely type of material to replace rare earth permanent magnets on a large scale. Iron nitride includes a variety of compounds such as FeN, Fe2N, Fe3N, Fe4N, among which α″-Fe 16 N2 compounds are the materials with the highest saturation magnetic induction intensity discovered so far, and have characteristics such as relatively high magnetocrystalline anisotropy, which almost meet all the requirements of high-performance magnets for material properties. 16 N2 is composed of Fe and N elements, with abundant reserves and low price, but it has poor stability at high temperatures and is easily decomposed above 200°C. The current preparation methods such as magnetron sputtering have great limitations in terms of output, purity and cost. The difficulty in the reduction nitridation method lies mainly in how to achieve nitridation of iron in an extremely low temperature range below the decomposition temperature.

[0003] In the prior art, the nitriding process is mainly promoted by refining the iron powder particle size, and is assisted by strengthening means such as reaction pressure or external field. For example, a Chinese patent (publication number: CN105861978A) discloses a mechanical ball milling method for preparing nitrided iron magnetic powder. ) discloses Fe as a permanent magnet 16 The preparation method of N2 compound, Chinese patent (publication number: CN106086776A) discloses a low temperature plasma nitriding method for preparing nitrided iron magnetic powder, etc. In general, the α″-Fe 16N2 materials are mostly ultra-thin coatings or nano-sized particles, which are not suitable for forming high-performance magnets by pressing or bonding. Especially when preparing large particle products, their purity cannot be guaranteed. Therefore, the existing α″-Fe 16 There is an urgent need to improve the purity and particle size of N2 substances. Summary of the Invention

[0004] It is difficult to prepare high-purity α"-Fe with micron-sized particles in the existing technology. 16 N2 and other technical problems, the purpose of the present invention is to provide a micron-sized, high-purity α "-Fe 16 A method for preparing N2 iron nitride magnetic powder.

[0005] The large-size high-purity α"-Fe 16 N2 iron nitride magnetic powder, where "large size" refers to micron-sized particles, preferably 5-40 μm, more preferably 10-30 μm. "High purity" refers to a pure phase iron nitride mass content of 97% or more, preferably 98% or more.

[0006] In order to achieve the above technical objectives, the present invention provides a large-sized high-purity α"-Fe 16 The method for preparing N2 iron nitride magnetic powder comprises the following steps:

[0007] 1) The iron ore concentrate is sequentially subjected to a high-pressure roller mill, a nano-sand mill, and a drying process to obtain micron-sized fine-particle iron oxide powder. The high-pressure roller milling process comprises the following conditions: a feed particle size of the iron ore concentrate of 40 to 100 µm, a roller spacing of 100 to 150 µm, a roller pressure of 10 to 20 MPa, and a high-pressure roller cycle of 1 to 5 times. The nano-sand milling process comprises the following conditions: a bead diameter of 0.05 to 0.5 mm, a grinding speed of not less than 2000 rpm, a grinding time of not more than 30 minutes, water as the grinding medium, and a solid-liquid mass-to-volume ratio of 1 g:0.5 to 3 mL. The drying process comprises vacuum drying at an air pressure of 90 to 100 kPa and a temperature of 60 to 100°C.

[0008] 2) hydrogen reducing the micron-sized fine iron oxide powder to obtain porous active reduced iron powder; the hydrogen reduction temperature is controlled to be within 50° C. below the critical temperature of the reduction conversion path, wherein the critical temperature of the reduction conversion path refers to the temperature at the intersection of the iron oxide hydrogen reduction fork curve;

[0009] 3) The porous active reduced iron powder is nitrided in an ammonia atmosphere to obtain α″-Fe 16 N2 iron nitride.

[0010] The technical solution of the present invention can obtain large-sized high-purity α"-Fe 16The key to N2 nitride iron magnetic powder is to obtain micron-sized iron particles with porous structure, high specific area and high activity by controlling the reduction process of iron concentrate. The iron particles with this structure are more conducive to low-temperature nitriding process and nitriding reaction, thereby obtaining high-purity phase and large-sized α″-Fe 16 N2 nitride iron magnetic powder. More specifically, the technical solution of the present invention first uses the technical means of high-pressure roller milling and nano-sand milling to coordinate mechanical activation of iron concentrate to prepare high-activity micron-sized iron oxide powder, wherein the high-pressure roller milling process hardly changes the particle size of the iron concentrate, mainly causing cracks on the surface of the iron concentrate, reducing its mechanical strength and increasing its reaction activity. Its activation mechanism for the iron concentrate mainly comes from the extrusion and shearing effect under high pressure between the rollers, which can change the surface properties of the iron concentrate. Nano-sand milling activates the iron concentrate by impacting and grinding the iron concentrate on a high-speed rotating grinding disc through a medium. The nano-sand milling process significantly changes the particle size of the iron concentrate. Therefore, the activation mechanisms of nano-sand milling and high-pressure roller milling are opposite and complementary. The present invention combines the two technical means of high-pressure roller milling and nano-sand milling to activate the iron concentrate, which can give it great activation energy storage and ensure that the iron concentrate has a micron-sized particle size. On this basis, by strictly controlling the hydrogen reduction temperature, the hydrogen reduction process conversion path is controlled to Fe3O4→Fe, thereby obtaining porous active reduced iron powder, which is beneficial to improve the reaction activity and rate of the low-temperature nitriding process, and then quickly react to obtain micron-sized, high-purity α″-Fe 16 N2 iron nitride.

[0011] As a preferred embodiment, the iron concentrate has a total iron content of 71.5% or greater by mass. Iron concentrate is a pure iron concentrate, primarily comprising deep beneficiation concentrate and iron, phosphorus, and iron slag from metallurgical processing. It is characterized by a total iron content of 71.5% or greater, with the remaining impurities being silicon, manganese, aluminum, and their oxides. Based on existing beneficiation methods, iron concentrate with a total iron content of 71.5% or greater is readily available and is a relatively inexpensive iron raw material.

[0012] The high-pressure roller mill of the present invention is adaptable to a wide range of iron ore concentrate particle sizes and can be used directly with iron ore concentrates that have been beneficiated or initially processed to a particle size of 40-100 µm. The roller spacing is primarily determined by the feed particle size of the iron ore. The key to high-pressure roller milling is the pressure between the rollers, which significantly influences the grinding and activation effect. The preferred pressure range is 15-20 MPa. Due to the significant edge effect of high-pressure roller mills, iron ore concentrates are subjected to two to four grinding cycles to achieve optimal roller pressure.

[0013] The nano-sand milling of the present invention can give iron concentrate rich mechanical energy storage and active sites, and the further preferred bead diameter range is 0.05~0.2mm. The further preferred grinding speed range is 2500~3000r / min. Based on the low strength of the iron concentrate after high-pressure roller milling, it is easy to cause over-grinding under the high-speed grinding effect of nano-sand milling, so it is necessary to control it within a very short grinding time to complete activation. The grinding time is controlled within 30min, which will not cause excessive refinement of the particles. The further preferred grinding time is 10~20min. In addition, since the high-pressure roller milling changes the hydrophilicity of the surface of the iron concentrate particles, water can be selected as the medium during the nano-sand milling process, and there is no need to add grinding aids, dispersion and other additives, which can avoid the introduction of new impurities as much as possible. The present invention grinds large-particle materials with mismatched small grinding beads and activates the materials in combination with roller milling, so that the iron concentrate can be activated in a short time and retains the micron-level particle size characteristics.

[0014] The drying and dehydration process of the present invention reduces the water content of the iron ore concentrate, facilitating the subsequent hydrogenation process. Low-temperature vacuum drying helps prevent particle agglomeration, and this drying method often results in a porous and loose structure, which is conducive to subsequent gas-solid reactions. If the iron ore concentrate material clumps after drying, it can be broken up using conventional methods such as ultrasound and grinding.

[0015] As a preferred embodiment, the micron-sized fine iron oxide powder has a particle size of 10-30µm and an activated lattice size of 150-800Å. While the iron concentrate undergoes synergistic activation by high-pressure roller milling and nano-sand milling, its particle size does not undergo significant refinement. However, the mechanical activation effect is quite significant. XRD analysis reveals a refinement of the activated lattice size to 150-800Å, indicating that the reactivity of the iron concentrate has been greatly enhanced, facilitating the subsequent hydrogen reduction process.

[0016] As a preferred solution, the conditions for hydrogen reduction are: the temperature is 20~50℃ lower than the critical temperature of the reduction conversion path, and the time is 2~5h. Generally speaking, in the process of preparing iron powder by hydrogen reduction of iron concentrate, in order to ensure the reduction efficiency of iron concentrate, the hydrogen reduction temperature is controlled to be higher than the critical temperature of the reduction conversion path. The key to the technical solution of the present invention is to control the hydrogen reduction temperature to be 20~50℃ lower than the critical temperature of the reduction conversion path. For example, the critical temperature of the reduction conversion path of a certain micron-sized iron concentrate is 500℃, and the technical solution of the present invention controls the hydrogen reduction temperature to be lower than the critical temperature of the reduction path conversion (preferably reduced at a temperature of 450~480℃), so that the reduction path follows the Fe3O4→Fe reduction path, rather than the Fe3O4→FeO→Fe reduction path. The Fe3O4→Fe reduction path can make the iron concentrate particles expand during the reduction process, and the particle size increases. After reduction, the iron concentrate particles are 12~35µm, and the particles show an embedded porous structure, with developed voids deep inside the particles, and their specific surface area is not less than 10m 2 / g, with a preferred specific surface area range of 20-30 m 2 / g. However, the reduction temperature cannot be too low, otherwise it will be difficult to completely reduce the iron oxide within a suitable time. During the hydrogen reduction process, micron-sized fine iron oxide powder is loosely distributed on the reactor, with a typical layer thickness of 1-5mm.

[0017] As a preferred solution, the critical temperature of the reduction path conversion of the micron-sized fine-particle iron oxide powder relative to the iron concentrate is reduced to 350~520℃ based on the activation effect of high-pressure roller milling and nano-sand milling. The method for determining the critical temperature of the reduction path conversion of the present invention is: 1) Theoretical calculation method, based on the mechanical activation theory and XRD detection, calculates the amount of mechanical energy stored in the activation process, and calculates the energy storage of iron oxide in combination with Gibbs free energy. The temperature point compared with the curve is the critical temperature. 2) Experimental detection method, testing the composition of the material phase of the reduction process at different reduction temperatures, and the temperature point where the FeO phase does not appear below a certain temperature is the critical temperature. According to the actual grinding energy storage situation, this temperature point is between 350~520℃, which is about 20~220℃ lower than the critical temperature point of 570℃ for the reduction path conversion of conventional iron concentrate.

[0018] As a preferred solution, the nitriding conditions are: ammonia pressure not higher than 0.5 MPa, nitriding temperature 170-195°C, and time 8-15 hours. Based on the micron-sized iron particles with porous structure, high specific area and high activity, the nitriding process becomes easier to produce α″-Fe 16 The purity of N2 iron nitride is above 97%, preferably above 98%. The ammonia atmosphere is more preferably a pure ammonia atmosphere.

[0019] Compared with the existing technology, the technical solution of the present invention brings the following beneficial technical effects:

[0020] 1) α″-Fe prepared by the present invention 16 N2 iron nitride magnetic powder is the material with the greatest potential to replace rare earth permanent magnets on a large scale. Compared to existing rare earth permanent magnets, this product offers advantages such as abundant raw material reserves, low price, ample supply, large-scale production, and a green production process, eliminating the need to worry about rare earth element quotas or resource depletion.

[0021] 2) The present invention prepares pure phase and highly amorphous α″-Fe 16 N2 iron nitride magnetic powder has a higher coercive force than similar products, and has a "giant magnetic moment" phenomenon, with the best saturation magnetization intensity. The improved comprehensive magnetic performance may be better than rare earth permanent magnet materials, and is suitable for fields such as electric vehicles and wind power generation facilities that have higher requirements for magnetic performance.

[0022] 3) The present invention prepares larger (micrometer-scale) pure phase α″-Fe 16 N2 magnetic powder particles have reached the processing and molding particle size range of existing technologies for rare earth magnetic powder. Compared with the currently prepared microscopic iron nitride, it is more suitable for magnetic powder pressing and bonding and other material processing, and has higher practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a thermodynamic calculation diagram of the mechanical energy storage of the 6-15µm iron concentrate obtained by high-pressure roller milling and nano-sand milling in Example 1. It can be seen from the figure that due to the existence of activated energy storage, the conversion temperature of the reduction path is converted from 571°C to 465°C.

[0024] Figure 2 This is the apparent image of the micron-sized iron concentrate obtained by high-pressure roller milling and nano-sand milling in Example 1 after hydrogen reduction; it can be seen from the figure that the iron powder has a porous structure, which is extremely beneficial to the gas permeation in the subsequent solid-gas reaction process.

[0025] Figure 3 The α″-Fe prepared in Example 1 16 XRD pattern of N2 material; the figure shows α″-Fe 16 N2 is a pure phase product with almost no other impurities, indicating a high degree of nitriding.

[0026] Figure 4 This is a scanning electron microscope image of the iron powder prepared in Control Example 1; as can be seen from the figure, the surface of the iron powder is sintered, with a high degree of density and low reaction activity, which is not conducive to the subsequent solid-gas reaction process.

[0027] Figure 5 α"-Fe prepared in Comparative Example 1 16XRD diagram of N2 material; it can be seen from the figure that due to the insufficient activity of iron powder, the nitriding reaction is still not sufficient after a long period of nitriding, and the material is mainly Fe phase.

[0028] Figure 6 α"-Fe prepared in Comparative Example 2 16 N2 material XRD pattern; it can be seen from the figure that α″-Fe 16 The purity of N2 is not high, which means that the activation degree of a single activation method is not high, and the purity of the prepared product is lower at the same level. DETAILED DESCRIPTION

[0029] In order to more clearly understand the present invention, the content of the present invention is now more clearly explained and analyzed using specific embodiments, but the claims of the present invention are not limited to the following example methods and conditions. Other examples obtained by relevant technical personnel in the field without creative work are all within the scope of protection of the present invention.

[0030] Example 1

[0031] The raw material is high-quality iron scale from the steel mill. The purity is 72.1% iron, and the total content of other impurities (acid insoluble matter) is only 0.3%. The test results show that the main component is high-purity iron oxide. The difference from iron concentrate is that there is more Fe2O 3, After testing, the particle size of more than 96% of the ore was between -200 mesh (200 mesh sieve) and +325 mesh (325 mesh sieve). The high-pressure roller mill was set with a roller spacing of 150µm and a roller pressure of 12MPa. The feed rate was set appropriately and the mill was circulated for 5 times. After testing, the particle size D 50 The material was then finely ground in a nano sand mill. A high-efficiency pin-type nano sand mill was selected with a rotation speed of 2000 r / min, 0.1 mm zirconia balls as the grinding beads, water as the solvent, and a solid-liquid ratio of 1 g: 3 mL. After grinding for 10 min, the particle size D 50 =30µm ultrafine particle slurry was dried at low temperature vacuum (95KPa, 80℃) for 3 hours to obtain powder.

[0032] The powder lattice size was found to be approximately 420Å by testing the powder lattice characteristics and other properties. The changes in the hydrogen reduction thermodynamic diagram after activation were calculated by combining the mechanical activation energy and other key parameters. Figure 1 As shown in Figure 2, the critical temperature of the reduction conversion path is approximately 465°C.

[0033] During the powder reduction stage, the reduction temperature was controlled at 430°C. The agglomerates were loosely distributed on a reduction steel belt with a height of 2mm. Pure hydrogen was used as the reducing gas and the reduction was carried out for 3 hours. After the reduction was completed, the iron powder had slightly agglomerated. After subsequent breaking up, the iron powder purity was tested to be 99%. The powder was placed in a tubular reactor and pure ammonia was introduced to control the pressure at around 0.2MPa. The pure phase sample was obtained by nitriding at 175°C for 15 hours. After XRD quantitative calculation, the pure phase α″-Fe 16 The purity of N2 magnetic powder is 98.6%.

[0034] Example 2

[0035] The super iron concentrate obtained by deep beneficiation is selected as raw material, with an iron grade of 72.1% and the total content of other impurities (acid insoluble matter) is only 0.3%. The particle size of the material after deep beneficiation is small. After testing, the particle size of more than 96% after beneficiation is between -200 mesh and +325 mesh. Set the high-pressure roller mill with a roller spacing of 100µm and a roller pressure of 18MPa. Set the appropriate feed rate and grind once. After testing, the particle size D after grinding is 50 The material was finely ground in a nano sand mill. A high-efficiency pin-type nano sand mill was selected with a rotation speed of 2500 r / min, 0.05 mm zirconia balls as the grinding beads, water as the solvent, and a solid-liquid ratio of 1 g:0.5 mL. After grinding for half an hour, an ultrafine particle slurry with a particle size of D50 = 20 μm was obtained. The powder was dried at a low temperature in vacuum (93 KPa, 70 ° C) for 5 hours.

[0036] By testing the powder lattice characteristics and other properties, the powder lattice size was measured to be 154Å. Combined with other lattice parameters, the lattice energy storage was calculated through mechanical activation theory and supported by experimental data, the critical temperature of the reduction conversion path is about 350℃.

[0037] During the powder reduction stage, the reduction temperature was controlled at 300 °C. The agglomerates were loosely distributed on the reduction steel belt with a height of 1 mm. Pure hydrogen was used as the reducing gas for 5 h. After the reduction, the iron powder had slightly agglomerated. After subsequent breaking up, the purity of the iron powder was tested to be 99.15%, and the particle size was about 25 μm. The morphology of the iron powder is shown in the figure below. Figure 2 The powder was also placed in a belt reactor with a thickness of 3 mm. The reaction temperature was controlled at 195 ° C. The pure phase sample was obtained by nitriding in pure ammonia at normal pressure for 8 hours. The XRD pattern of the sample was as follows: Figure 3 As shown, there are almost no other impurities. After XRD quantitative calculation, the pure phase α″-Fe 16 The purity of N2 magnetic powder is 99.2%.

[0038] Example 3

[0039] The same super iron concentrate as in Example 2 was used as the raw material. The raw material was first subjected to high-pressure roller milling (HPGM) with a roller spacing of 130 µm and a roller pressure of 20 MPa. The milling process was performed three times at an appropriate feed rate. The material was then finely ground in a nano-sand mill using a high-efficiency pin-type nano-sand mill at a speed of 3000 r / min, 0.2 mm zirconia balls, water as the solvent, and a solid-liquid ratio of 1 g:1 mL. After grinding for 15 minutes, an ultrafine particle slurry with a particle size D50 of 22 µm was obtained. The slurry was then dried at a low temperature (93 kPa, 100°C) under vacuum for 2 hours to obtain a powder.

[0040] By testing the powder lattice characteristics and other properties, the powder lattice size was measured to be 621Å. Combined with other lattice parameters, the lattice energy storage was calculated through mechanical activation theory and supported by experimental data. After activation, the intersection temperature of the fork curve of its hydrogen reduction thermodynamic diagram was 495℃.

[0041] During the powder reduction stage, the reduction temperature was controlled at 450°C. The agglomerates were loosely distributed on the reduction steel belt with a height of 3mm. Pure hydrogen was used as the reducing gas and the reduction was carried out for 3 hours. After the reduction was completed, the iron powder had slightly agglomerated. After subsequent breaking up, the iron powder purity was tested to be 98.85%, and the particle size was approximately 25µm. The powder was also placed in a belt reactor with a thickness of 2mm. The reaction temperature was controlled at 195°C and nitrided under pure ammonia at normal pressure for 11 hours to obtain a pure phase sample with almost no other impurities. After XRD quantitative calculation, the obtained pure phase α″-Fe 16 The purity of N2 magnetic powder is 98.4%.

[0042] Example 4

[0043] The same super iron concentrate as in Example 2 was used as the raw material. The raw material was first subjected to high-pressure roller milling (HPGM) with a roller spacing of 130 µm and a roller pressure of 15 MPa. The milling process was performed four times at an appropriate feed rate. The material was then finely ground in a nano-sand mill using a high-efficiency pin-type nano-sand mill at a speed of 2700 r / min, 0.5 mm zirconia balls, and water as the solvent at a solid-liquid ratio of 1 g:2 mL. After grinding for 30 minutes, an ultrafine particle slurry with a particle size D50 = 27 µm was obtained. The slurry was then dried at a low temperature (93 kPa, 100°C) under vacuum for 2 hours to obtain a powder.

[0044] By testing the powder lattice characteristics and other properties, the powder lattice size was measured to be 800Å. Combined with other lattice parameters, the lattice energy storage was calculated through mechanical activation theory and supported by experimental data. After activation, the temperature of the fork curve intersection of its hydrogen reduction thermodynamic diagram was 520℃.

[0045] During the powder reduction stage, the reduction temperature was controlled at 500°C. The agglomerates were loosely distributed on the reduction steel belt with a distribution height of 5mm. After reduction for 5 hours, the iron powder had slightly agglomerated. After subsequent breaking up, the iron powder purity was tested to be 98.65%, with a particle size of approximately 30µm. The powder was also placed in a belt reactor with a distribution thickness of 1mm. The reaction temperature was controlled at 195°C. Ammonia was introduced at a pressure of 0.5MPa. A pure phase sample was obtained by nitriding under pure ammonia at atmospheric pressure for 13 hours. Almost no other impurities were found in the sample test. After XRD quantitative calculation, the obtained pure phase α″-Fe 16 The purity of N2 magnetic powder is 97.8%.

[0046] Comparative Example 1

[0047] This control example is mainly used to illustrate the difference between controlling the hydrogen reduction temperature within and outside the critical temperature range of the hydrogen reduction path conversion.

[0048] Compared with Example 1, the only difference is that the hydrogen reduction temperature is set to 500 ° C, which is higher than the critical temperature of the reduction conversion path, and is not lower than the critical temperature of the reduction conversion path within the range of 20 to 50 ° C as required. The morphology image of the iron powder after hydrogen reduction is as follows: Figure 4 As shown in the figure, the iron powder surface has no deep pores, which will limit the ammonia permeation reaction. The iron powder is nitrided under the same conditions as in Example 1 to obtain α″-Fe 16 N2 sample, α″-Fe 16 The XRD pattern of N2 sample is as follows Figure 5 As shown, the product purity is low.

[0049] Comparative Example 2

[0050] This comparative example is mainly used to illustrate that it is difficult to fully activate iron concentrate by using a single high-pressure roller mill or nano-grinding.

[0051] Compared with Example 1, the only difference is that only high-pressure roller milling is used, and the roller mill material is not subjected to nano-sand grinding, and hydrogen reduction is directly performed. The results show that the activation purity of a single high-pressure roller mill is insufficient, and it requires a temperature above 700°C for rapid reduction. In addition, the obtained iron powder is agglomerated and has a small specific surface area, making it difficult to complete the subsequent nitriding process.

[0052] Comparative Example 3

[0053] This comparative example is mainly used to illustrate that it is difficult to fully activate iron concentrate by using a single high-pressure roller mill or nano-grinding.

[0054] Compared with Example 1, the only difference is that only nano-sand milling is used, and the iron ore concentrate is not subjected to high-pressure roller milling. After nano-sand milling, hydrogen reduction is performed. The results show that the activation degree of single impact and grinding is insufficient. Without the cooperation of high-pressure roller milling, the same grinding conditions can achieve a critical temperature of about 480°C, and the activation characteristics such as cracks of the particles are less. The XRD images of the products prepared after reduction and nitridation under the same conditions are as follows: Figure 6 shown.

[0055] Comparative Example 4

[0056] Compared with Example 1, the only difference is that the nano-grinding conditions are different: the solid-liquid mass volume ratio is 1g:10mL, ethanol is used as the medium, 0.3 and 0.5mm grinding beads are added to the original 0.05mm grinding beads to achieve a 3:4:3 ratio, and the grinding time is set to 4h. At this time, the grinding activation degree is higher than that of Example 1, and the critical temperature of the reduction conversion path can reach below 400℃, which can prepare pure phase α″-Fe 16 N2, but the particle size is only about 100nm, which makes it difficult to realize the subsequent magnetization and pressing process of magnetic powder.

Claims

1. A large-sized, high-purity α″-Fe 16 The method for preparing N2 iron nitride magnetic powder is characterized by: The following steps are involved: 1) The iron ore concentrate is sequentially subjected to high pressure roller milling, nano sand milling and drying treatment to obtain micron-sized fine particle iron oxide powder; the conditions of the high pressure roller mill are: the feed particle size of the iron ore concentrate is: 40-100µm, the roller spacing is 100-150µm, the roller pressure is 10-20MPa, and the number of high pressure roller cycles is 1-5 times; the conditions of the nano sand mill are: the diameter of the grinding beads is 0.05mm-0.5mm, the grinding speed is not less than 2000r / min, the grinding time is not more than 30min, the grinding medium is water, and the solid-liquid mass volume ratio is 1g:0.5-3mL; the conditions of the drying treatment are: vacuum drying method, air pressure is 90-100KPa, and temperature is 60-100℃; 2) hydrogen reduction of micron-sized fine-particle iron oxide powder to obtain porous active reduced iron powder; the hydrogen reduction temperature is controlled to be within 50° C. below the critical temperature of the reduction conversion path, wherein the critical temperature of the reduction conversion path refers to the temperature at the intersection of the iron oxide hydrogen reduction fork curve; 3) The porous active reduced iron powder is nitrided in an ammonia atmosphere to obtain α″-Fe 16 N2 Iron Nitride.

2. A large-sized high-purity α″-Fe according to claim 1 16 The method for preparing N2 iron nitride magnetic powder is characterized by: The total iron content of the iron concentrate is above 71.5%.

3. A large-sized high-purity α″-Fe according to claim 1 or 2 16 The method for preparing N2 iron nitride magnetic powder is characterized by: The particle size of the micron-sized fine-particle iron oxide powder is 10-30 μm, and the activated lattice size is 150-800 Å.

4. A large-sized high-purity α″-Fe according to claim 1 or 2 16 The method for preparing N2 iron nitride magnetic powder is characterized by: The conditions for hydrogen reduction are: the temperature is 20-50° C. lower than the critical temperature of the reduction conversion path, and the time is 2-5 hours.

5. A large-sized high-purity α″-Fe according to claim 1 or 2 16 The method for preparing N2 iron nitride magnetic powder is characterized by: The critical temperature of the reduction path conversion of the micron-sized fine-particle iron oxide powder to iron concentrate is reduced to 350-520° C. based on the activation effect of the high-pressure roller mill and the nano-sand mill.

6. A large-sized high-purity α″-Fe according to claim 1 or 2 16 The method for preparing N2 iron nitride magnetic powder is characterized by: The nitriding conditions are as follows: the ammonia pressure is not higher than 0.5 MPa, the nitriding temperature is 170-195° C., and the time is 8-15 hours.